Education on the Application of Electrical Technology Through Creative Learning Projects: Pendidikan tentang Penerapan Teknologi Listrik Melalui Proyek Pembelajaran Kreatif - Ayu Mika Sherila; Ni Putu Devira Ayu Martini; Achmad Zuchriadi; Yosy Rahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid advancement of technology demands innovative approaches in education to equip students with essential STEM competencies. Specific Background: In Indonesia, high school learning of electrical engineering is still dominated by theoretical instruction with limited opportunities for hands-on practice, resulting in low engagement and inadequate technical skill development. Knowledge Gap: Few initiatives integrate real-world electrical engineering applications into secondary education through creative, project-based learning. Aim: This study reports on the implementation and evaluation of a creative learning outreach program conducted by Universitas Pembangunan Nasional Veteran Jakarta at SMA Negeri 66 Jakarta, designed to enhance students’ understanding of electrical technology. Results: The program engaged 72 students through three interactive modules: portable solar power storage, a mechatronic sumo robot, and IoT-based drowsiness detection glasses. Evaluation results showed a 28% increase in interest toward STEM careers, a 35% improvement in conceptual understanding, and positive perceptions of program delivery. Novelty: Unlike conventional lectures, this initiative combined project-based learning with real-world prototypes, directly linking theory with application and fostering creativity, collaboration, and problem-solving. Implications: These findings highlight the value of integrating interactive, technology-driven projects into secondary education, offering a scalable model for strengthening STEM literacy and preparing future engineers.Highlight : Hands-on modules (solar power, sumo robot, IoT glasses) increased student engagement. Survey showed 28% higher STEM interest and 35% better understanding of technology. Program effectively connected theory with real-world applications in electrical engineering. Keywords : Education, Creative Learning Project, Electrical Technology, Project-Based Learning, STEM